The effects of two different resisted swim training load protocols on swimming strength and performance - González Ravé, J. M.; Legaz-Arrese, A.; González-Mohino, F.; Yustres , I.; Barragán, R.; de Asis Fernández, F.; Juárez, D.; Arroyo-Toledo, J. J. (Journal of Human Kinetics, 2018)
This study used a power rack device to evaluate the effects of 2 different approaches to resisted swim training loads on swimming strength and performance. Sixteen male, youth national-level swimmers (mean age, 16.22 ± 2.63 years; body height, 169 ± 10.20 cm; body mass, 61.33 ± 9.90 kg) completed a 6-week specific strength-training program, and were then randomly assigned to one of the two groups: a standard training group (GS, n = 8) and a flat pyramid-loading pattern group (GP, n = 8). Strength and power tests along with specific swimming tests (50-m crawl and 50-m competition-style time trials) were conducted at baseline (pre-test), before the third week (mid-test), and after 6 weeks of intervention (post-test). Isokinetic swim bench tests were conducted to obtain measurements of force production and power, and 1RM tests with the power rack system were conducted to measure the maximum drag load (MDL) and specific swimming power. Following 6 weeks of intervention, the mean MDL increased (p < 0.05) by 13.94%. Scores for the 50-m competition style and 50-m crawl time trials improved by 0.32% and 0.78%, respectively, in the GP; however, those changes were not statistically significant. The GS significantly increased their time in the 50-m competition style by 2.59%, and their isokinetic force production decreased by 14.47% (p < 0.05). The 6-week strength-training program performed with the power rack device in a pyramidal organization was more effective than a standard linear load organization in terms of producing improvements in the MDL; however, it did not produce significant improvements in performance. The use of a strength-training program with a pyramidal organization can be recommended for specific strength-training in young swimmers during a preparatory period. However, in our study, that program did not produce significant changes in 50-m crawl and main competition style performance.